Relapse after treatment withdrawal of antiepileptic drugs for juvenile absence epilepsy and juvenile myoclonic epilepsy - Healy, Liam; Moran, Maria; Singhal, Sumeet; O'Donoghue, Michael F; Alzoubidi, Rania; Whitehouse, William P. (Elsevier, 2018)
Purpose Conventional teaching is that juvenile myoclonic epilepsy (JME) and juvenile absence epilepsy (JAE) require lifelong antiepileptic drug (AED) treatment. We therefore wanted to determine how many patients attending our epilepsy service with JAE or JME went into 2 year remission, and then relapsed, both off and on AEDs.